INFLUENCE OF SOCIAL ENVIRONMENT AND LIFESTYLE FOR COMMUNITY CONSUMPTION BEHAVIOR IN THE PANDEMIC COVID 19 - Eko Hadi Wiyono (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
The purpose of this study was to determine: (1) the influence of the social environment on people's consumption behavior on the covid pandemic 19. (2) The influence of lifestyle on people's consumption behavior on the covid pandemic 19. (3) the influence of the social environment and lifestyle on behavior public consumption in this pandemic occurs. The research method used in this study is a descriptive method with a quantitative approach. The population in this study is the Palmerah village community. The sample used was 128 people. The analysis technique used is multiple linear regression analysis. Based on the results of the study concluded that: public consumption during the covid pandemic 19. The coefficient of determination (adjusted R2) of 0.095, meaning that 9.5% of people's consumption behavior is influenced by the social environment and lifestyle, while the remaining 90.5% is influenced by other factors.